Loratadine Loaded Chitosan Tannic Acid Nanoparticles as Anti-Proliferative Agent Against Breast Cancer: In-silico, in-vitro and Cell Studies - Ali IH; Al-Tabakha MM; Khalil IA (International Journal of Nanomedicine)
Isra H Ali,1,2 Moawia M Al-Tabakha,3,4 Islam A Khalil5 1Department of Pharmaceutics, Faculty of Pharmacy, University of Sadat City, Sadat City, Egypt; 2Nanomedicine Laboratory, Faculty of Pharmacy, University of Sadat City, Sadat City, Egypt; 3Department of Pharmaceutical Sciences, College of Pharmacy and Health Sciences, Ajman University, Ajman, United Arab Emirates; 4Centre of Medical and Bio-Allied Health Sciences Research Centre, Ajman University, Ajman, United Arab Emirates; 5Department of Pharmaceutics, College of Pharmaceutical Sciences and Drug Manufacturing, Misr University for Science and Technology, 6th of October City, Giza, EgyptCorrespondence: Islam A Khalil, Department of Pharmaceutics, College of Pharmaceutical Sciences and Drug Manufacturing, Misr University for Science and Technology, 6th of October City Giza, 12582, Egypt, Email islam.khalil@must.edu.eg; islamkhll@gmail.com Moawia M Al-Tabakha, Department of Pharmaceutical Sciences, College of Pharmacy and Health Sciences, Ajman University, P.O. Box 346, Ajman, United Arab Emirates, Email m.altabakha@ajman.ac.aePurpose: This study aims to prepare Loratadine-loaded chitosan/tannic acid nanoparticles (LOR-CS/TAN NPs) through ionic gelation to be used as an anti-proliferative agent to aid in overcoming breast cancer propagation.Methods: First, in-silico virtual screening was carried out to select the most appropriate anti-histaminic drug based on its inhibitory effect on the H1-histamine receptor, resulting in the selection of Loratadine (LOR). Molecular interaction between LOR with chitosan (CS), a positively charged polymer, and hyaluronan, a negatively charged polymer, was investigated separately through molecular docking, leading to the selection of CS. Optimization was carried out using Box Behnken Design, with concentrations of CS, LOR, and tannic acid (TAN) as independent variables. The optimized nanoparticles were then examined through morphological and physicochemical studies. Cell studies against the MCF-7 breast cancer cell line were conducted to assess cytotoxicity, cell cycle, apoptosis, and necrosis.Results: The optimum formulation was determined to be CS (0.2% w/v), LOR (1:2 weight ratio to CS), and TAN (1:30.6 weight ratio to CS). The optimized LOR-CS/TAN NPs exhibited a size of 283 nm, a polydispersity index (PDI) of 0.102, and an entrapment efficiency of 78%, along with sustained drug release for 24 hours. The results demonstrated that LOR-CS/TAN NPs possess higher anti-cancer activity compared to free LOR. This enhanced activity is attributed to the synergistic effect of the drug and the designed nanoparticle, particularly due to the presence of tannic acid.Conclusion: In conclusion, Loratadine-loaded chitosan/tannic acid nanoparticles (LOR-CS/TAN NPs) demonstrated enhanced anti-cancer activity against the MCF-7 breast cancer cell line. The synergistic effect of Loratadine and the nanoparticle system, particularly due to the presence of tannic acid, resulted in higher cytotoxicity compared to free Loratadine. These findings suggest that LOR-CS/TAN NPs have significant potential as a novel anti-proliferative agent for breast cancer therapy. Keywords: loratadine, chitosan, tannic acid, nanoparticles, breast cancer, in-silico